1985
DOI: 10.1128/iai.49.2.402-406.1985
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of assembly and decay of complement components on Escherichia coli O111:B4 preparation of stable intermediates

Abstract: The preparation of bacterial intermediates bearing complement components at various steps of the complement sequence was investigated by suspending immunoglobulin M-opsonized Escherichia coli Oll1:B4 cells in complement-deficient sera at different temperatures and ionic strengths. The optimal conditions for the formation of the intermediates at T,n were found to be an ionic strength of 0.091 , and a temperature of 37°C, except for BAC142, which could be formed equally well at room temperature. In contrast to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The reason 30 to 35% of BAC1-5 escaped killing by PNS or acetate extract could be explained neither by an intrinsic decay of BAC1-5 nor by an extrinsic decay induced by the soluble acetate extract. In fact, we previously showed that this BAC is rather stable (16), and the results presented in Fig. 3 indicate that its stability is not affected by incubation with the granule extract.…”
Section: Fig 4 (A)mentioning
confidence: 53%
See 3 more Smart Citations
“…The reason 30 to 35% of BAC1-5 escaped killing by PNS or acetate extract could be explained neither by an intrinsic decay of BAC1-5 nor by an extrinsic decay induced by the soluble acetate extract. In fact, we previously showed that this BAC is rather stable (16), and the results presented in Fig. 3 indicate that its stability is not affected by incubation with the granule extract.…”
Section: Fig 4 (A)mentioning
confidence: 53%
“…Buffers. Krebs-Ringer phosphate (KRP) buffer (pH 7.4; ionic strength, 0.091 pu) supplemented with 0.64 mM MgCI2 and 0.16 mM CaCl2 was prepared as previously described (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations